20th AIAA/CEAS Aeroacoustics Conference 2014
DOI: 10.2514/6.2014-3104
|View full text |Cite
|
Sign up to set email alerts
|

On the generation and propagation of multiple pure tones inside turbofans at transonic regime

Abstract: Whereas the sound radiated from the inlet of turbofans is mainly due to rotor-stator interactions in approach flight, the shock waves (or N-waves) emitted by the rotor at transonic rotation speeds can be a dominant noise source during takeoff and climb. The study of N-waves needs to take account of two main processes: (i) The generation of Nwaves for a perfect rotor (where all blades are identical) and for a real rotor (considering small geometrical blade dispersion); (ii) The N-wave propagation through the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The resulting acoustic character can be observed in the form of tonal sounds at integer multiples of the rotational frequency; thus, it is a super-harmonic type of noise. These conclusions were also stated by Sharma et al [39], Raitor and Neise [28] and Thisse et al [40]. The description of buzz-saw noise is still a current research topic, as this type of noise is dominant in aircraft engines.…”
Section: Buzz-saw Tonal Noisementioning
confidence: 57%
“…The resulting acoustic character can be observed in the form of tonal sounds at integer multiples of the rotational frequency; thus, it is a super-harmonic type of noise. These conclusions were also stated by Sharma et al [39], Raitor and Neise [28] and Thisse et al [40]. The description of buzz-saw noise is still a current research topic, as this type of noise is dominant in aircraft engines.…”
Section: Buzz-saw Tonal Noisementioning
confidence: 57%
“…It has been shown that this type of model can capture the main features of this pressure field [12][13][14], and propagation of input one-dimensional waveforms generated from measurements close to the fan [11,15] or by means of blade stagger angles values [16] show the reliability of the one-dimensional approximation of the pressure field. Prasad [17] compared the results based on such an approximation against three-dimensional numerical simulations and assessed the effect of the radial span of the pressure field.…”
mentioning
confidence: 99%